THE APPLICATION OF READING ALOUD METHOD TO IMPROVE STUDENTS' SKILLS IN GIVING LINES - Jannah, Rauzatul; Idris, Aisyah; Mazuki, Mazuki (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The issues contained in this thesis was how the selection of teaching methods that did not correspond to the MAS students Daruzzahidin Kuta Baro, Aceh Besar. The teacher asked the students to read the text and translate it. However, he was only paying attention to the truth of the translation with little consideration for the correct reading, both in terms of lines and pronunciations. This method showed the ineffectiveness and did not affect the correct reading of students, so that students were not able to read the text contained in their Arabic language books. The purpose of this study are to determine the increase of students ability to give the line by applying reading aloud method in MAS Daruzzahidin Kuta Baro, Aceh Besar. The Experiment method was used in this thesis by the researcher. In collecting data the researcher used some techniques, they are; observation and test. Best on this study, the application of reading aloud method can improve students' skills in corretc reading, both in terms of lines and pronunciations. This can be proved from the t-test value is -4.53 larger than t-table on the degree of 5% ie 2.11.